1997
DOI: 10.1111/j.1748-5827.1997.tb02983.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis and arthrosynovitis associated with Leishmania donovani infection in a dog

Abstract: A 10-month-old male maremma shepherd dog was presented with chronic diarrhoea, moderate polyuria/polydipsia, lethargy, dysorexia and stiffness. Pain was elicited in the distal parts of all four limbs. Radiographs of the limbs showed increased endomedullary radiopacity and lysis, with thick periosteal proliferations at the metadiaphyseal areas of each radius-ulna and tibia and of the distal metacarpus on one side. Polyclonal hypergammaglobulinaemia was documented and a similar electrophoretic protein pattern wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 2 publications
5
37
1
10
Order By: Relevance
“…Before the beginning of the treatment erythrocytic hypoplasia was observed in the bone marrow cytology of two of the dogs (28.6%), which agrees with the findings of Anosa and Idowu 30 , Yamaguchi et al 34 and Buracco et al 33 , who reported that animals with visceral leishmaniasis presented bone marrow hypoplasia, and also with the reports of Kontos and Koutinas 8 , Koutinas et al 9 , Ciaramella and Corona 2 and Ikeda et al 27 , who affirmed that the anemia in dogs with visceral leishmaniasis is nonregenerative. After the administration of meglumine antimoniate, all of the anemic animals presented a regenerative erythrocytic response, evidenced by an increase in the number of erythroid progenitor cells in the bone marrow, and by the presence of polychromatophilia, polychromatic rubricytes and metarubricytes in the peripheral blood.…”
Section: Results Discussion and Conclusionsupporting
confidence: 87%
See 4 more Smart Citations
“…Before the beginning of the treatment erythrocytic hypoplasia was observed in the bone marrow cytology of two of the dogs (28.6%), which agrees with the findings of Anosa and Idowu 30 , Yamaguchi et al 34 and Buracco et al 33 , who reported that animals with visceral leishmaniasis presented bone marrow hypoplasia, and also with the reports of Kontos and Koutinas 8 , Koutinas et al 9 , Ciaramella and Corona 2 and Ikeda et al 27 , who affirmed that the anemia in dogs with visceral leishmaniasis is nonregenerative. After the administration of meglumine antimoniate, all of the anemic animals presented a regenerative erythrocytic response, evidenced by an increase in the number of erythroid progenitor cells in the bone marrow, and by the presence of polychromatophilia, polychromatic rubricytes and metarubricytes in the peripheral blood.…”
Section: Results Discussion and Conclusionsupporting
confidence: 87%
“…An increase in the number of macrophages and monocytes shown by bone marrow cytology was not observed in any of the animals, which disagrees with the findings of Anosa and Idowu 30 , Yamaguchi et al 34 and Buracco et al 33 , who stated that an increase in the number of monocytes and macrophages is very frequent in dogs with visceral leishmaniasis. In the course of the experiment one of the alterations observed through the myelogram was the occurrence of plasmocytosis in two dogs, probably due to the antigenic stimulation provoked by the infection.…”
Section: Results Discussion and Conclusioncontrasting
confidence: 69%
See 3 more Smart Citations